Game Theory and the brain - van 't Wout, M. (Nervenheilkunde, 2011)
What is the neural basis of why you trust one person, but not the other? How do emotions in response to unfairness guide our interactions? What are the neural responses associated with cooperation? The field of social neuroeconomics aims to answer these and other questions to better understand the neural circuitry of decision-making in social interactions. In addition to neuroimaging studies, which can give insight into a possible correlation between brain activation and a cognitive process, (virtual) lesion studies allow drawing causal inferences about the role of a particular brain area in the social decisionmaking process. This paper will review some of the more recent findings on the neural basis of fairness, trust and cooperation identified using neuroimaging or lesion studies.
Keywords: Social interaction; decision-making; fairness; cooperation; trust